Impact of climate change on vegetable crop diseases in the Left-Bank Forest-Steppe of Ukraine - Mukha, B. (Scientific Progress & Innovations, 2025)
The aim of this review is to provide a comprehensive analysis of the impact of global climate change on the phytosanitary status of vegetable crop agrocenoses in the context of agroecosystem transformation in the Left-Bank Forest-Steppe of Ukraine. Based on long-term meteorological observations, a stable trend of climate aridization in the region has been identified, characterized by an increase in the mean annual temperature by 1.1 °C and a 5 % decrease in annual precipitation during 1991–2020 compared to previous periods. An increase in the frequency of drought conditions from 47 % to 61 % and greater thermal instability has been verified, manifesting in abrupt cold snaps (15.4 days/year) and extreme temperature fluctuations, particularly in spring. It was found that the prolongation of the growing season, the increase in accumulated effective temperatures, and the absence of stable winter chilling create conditions for: cultivating 2–3 harvests of vegetable crops; introducing overwintering vegetable crops in most regions of Ukraine; and producing ultra-early vegetable and melon crops and potatoes at reduced production costs. The review explores the mechanisms by which climate change affects the pathogenic complex of vegetable crops, including range expansion, shifts in epidemiological cycles, and increased aggressiveness of phytopathogens. The northward expansion of thermophilic pathogens (e.g., Fusarium oxysporum f. sp. lycopersici, Xanthomonas campestris pv. vesicatoria) has been recorded, and five new disease-causing agents have been identified in the region, including Acidovorax citrulli and Tomato brown rugose fruit virus. It has been established that the extended growing season enables the development of additional pathogen generations, while the coincidence of spring cold spells with summer hyperthermia and water deficit creates multistress conditions that suppress plant immunity. It is argued that climate change drives the transformation of phytopathosystems, promoting the emergence of new pathogen races with increased ecological plasticity and virulence. Given these findings, the Left-Bank Forest-Steppe should be considered a model testing ground for developing adaptive cultivation technologies and effective plant protection systems under a changing climate, which is vital for ensuring Ukraine’s food security.